1958
DOI: 10.1152/ajplegacy.1958.194.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Deprivation on the Metabolism of Fetal and Adult Tissues

Abstract: Fetal liver slices have a remarkably high rate of lipogenesis anaerobically as well as aerobically, shown by the incorporation of carbon-14 from pyruvate into lipids. In contrast, slices of adult or 1-day-old liver have a much lower lipogenetic rate anaerobically than aerobically. Fractionation of the fetal liver lipids showed that phospholipid and glyceride fatty acids are synthesized at essentially equal rates aerobically and anaerobically but cholesterol synthesis is much slower in nitrogen than in oxygen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1961
1961
1998
1998

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…No improvement in rates of lipogenesis in the IUGR fetus was found when maternal oxygen concentration was increased. This lack of effect of maternal oxygen supplementation on lipogenesis is consistent with studies by Villee and coworkers (21,22). They demonstrated that the effect of total oxygen deprivation on fktal lipogenesis varied with gestational age.…”
Section: Discussionsupporting
confidence: 91%
“…No improvement in rates of lipogenesis in the IUGR fetus was found when maternal oxygen concentration was increased. This lack of effect of maternal oxygen supplementation on lipogenesis is consistent with studies by Villee and coworkers (21,22). They demonstrated that the effect of total oxygen deprivation on fktal lipogenesis varied with gestational age.…”
Section: Discussionsupporting
confidence: 91%
“…Since the classical investigations of Needham on the metabolism of the developing chick embryo (24), considerable evidence has accumulated that suggests that carbohydrates are the major source of energy for immature organs (4,5). That this obtains in the heart is supported by the presence of higher levels of cardiac glycogen during fetal and neonatal growth than in adult life (25,26), and higher rates of activity in the newborn heart of some enzymes involved in carbohydrate metabolism (27).…”
Section: Methodsmentioning
confidence: 99%
“…For the tissues of the mammalian fetus, however, carbohydrates rather than lipids appear to serve as the primary source of energy (4,5). This difference in energy metabolism related to maturation suggested that the heart of the newborn, in contrast to that of the adult, might be unable to utilize long chain fatty acids and perforce must rely on glucose as the major substrate for energy production.…”
mentioning
confidence: 99%
“…However, proteins are probably used for synthesis rather than for oxidation in the fetus. Villee et al [38] demonstrated that fetal liver slices do oxidize some radioactive fat to 14 CO 2 although their data were not quantitative. One group studying intact fetuses [33] measured umbilical arterial-venous differences of glucose and fructose in lambs (125-135 days gestaticnal age) and concluded that glucose provides cne-half to one-sixth of the metabolic requirements of this preparation.…”
Section: Discussionmentioning
confidence: 96%
“…The comment has frequently been made that the mammalian fetus develops in a chronically hypoxic environment [38]. However, how the growing fetus with a low oxygen consumption can perform synthetic processes at a rapid rate is difficult to understand.…”
Section: Introductionmentioning
confidence: 99%